- Study on Species and Conservation Status of Knifefish (Family: Notopteridae) at Parung Ornamental Fish Market, Bogor Regency - Satria Yudha, Donan; Reza, Aulia Fachri (Berkala Ilmiah Biologi, 2024)
Indonesia hosts 4 endemic knifefish species namely: Chitala borneensis, Chitala hypselonotus, Chitala lopis, and Notopterus notopterus. The natural distribution of the four species includes Java, Riau, Sumatra, Jambi, Bengkulu, Lampung, and Kalimantan. Knifefish or belida (Notopteridae) is an ornamental fish that is fairly popular among Indonesian ornamental fish lovers. Overfishing activities in nature, as well as alterations and deterioration of the aquatic environment, can cause the sustainability of this fish to be endangered. The local knifefish population has declined, evidenced by data from the Riau Provincial Statistics Agency through data on the capture of belida fish (Chitala spp. and Notopterus spp.) in Riau in 2009. The research was conducted in February-April 2023 at Parung Ornamental Fish Market, Bogor Regency. The purpose of this study was to identify which knifefish species (Notopteridae) are traded in Parung Ornamental Fish Market, Bogor Regency; Conservation status of each knifefish species and the origin of knifefish traded in Parung Ornamental Fish Market, Bogor Regency. The method used was morphological comparison of fish and interviews. The results obtained show that there were 3 species of knifefish traded, 1 of them is a local species (N. notopterus) which is fully protected by the Decree of the Minister of Fisheries and Maritime Affairs Number 1 of 2021 with a conservation status of Least Concern (LC). The other two species are species from outside Indonesia (C. ornata with conservation status LC and C. blanci with conservation status Near Threatened (NT)). Local knifefish marketed by sellers come from the wild, strongly suspected to originate from Jambi area, precisely in Batanghari River basin and its tributaries. Meanwhile, the majority of non-local knifefish species are imported from Vietnam and Thailand, as well as several fish farm locations in the Parung area.